Selected aspects of low emission management in the Middle Odra Region = Ekonomiczne determinanty zarządzania niską emisją na obszarze Środkowego Nadodrza - Dzikuć, Maciej; Dzikuć, Maria (Zielona Góra: Faculty of Economics and Management Press)
According to the data of the European Environment Agency, due to excessive air pollution about 47 thousand people die prematurely every year in Poland. Although in recent years the level of industrial emissions in Poland has been significantly reduced, it is still a very serious problem of the so-called low emission. The aim of the paper was to determine the most important sources of low emission in the Middle Odra Region and to indicate activities that will optimally limit this problem.
Keywords: niska emisja; ekonomia; ekologia; Środkowe Nadodrze; low emissions; economy; ecology; Middle Odra Region